2019
DOI: 10.1111/ddi.13016
|View full text |Cite
|
Sign up to set email alerts
|

East is East and West is West: Population genomics and hierarchical analyses reveal genetic structure and adaptation footprints in the keystone species Paracentrotus lividus (Echinoidea)

Abstract: Aim The Atlanto‐Mediterranean edible purple sea urchin, Paracentrotus lividus, is a commercially exploited keystone species in benthic communities. Its browsing activity can deeply modify the littoral landscape, and changes in its abundance are of major conservation concern. This species is facing nowadays contrasting anthropogenic pressures linked to predator release, exploitation and sea warming. Management of this key species requires knowledge of its genetic structure, connectivity and local adaptation. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 84 publications
(119 reference statements)
7
42
0
Order By: Relevance
“…Nonetheless, for both species of Symphodus, the combination of the results of GWAS www.nature.com/scientificreports/ and RDA revealed a larger number of candidate loci, putatively under selection, as well as the selection drivers of most of the outlier loci. Redundancy analyses have been successfully used to detect signals of selection by comparing population allele frequencies to their environmental variables 4,6 . As we had individually based environmental data, we assessed how each single individual was distributed along the RDA axes based on its genotype, and according to its environmental predictors 42 .…”
Section: Genomic Associations To Phenotypic and Environmental Variablmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, for both species of Symphodus, the combination of the results of GWAS www.nature.com/scientificreports/ and RDA revealed a larger number of candidate loci, putatively under selection, as well as the selection drivers of most of the outlier loci. Redundancy analyses have been successfully used to detect signals of selection by comparing population allele frequencies to their environmental variables 4,6 . As we had individually based environmental data, we assessed how each single individual was distributed along the RDA axes based on its genotype, and according to its environmental predictors 42 .…”
Section: Genomic Associations To Phenotypic and Environmental Variablmentioning
confidence: 99%
“…Genotyping-by-sequencing (GBS) 8 , provides a cost-effective approach for population genomic studies on non-model species. This methodology provides high density of markers that may allow identifying non-neutral genomic signatures related to adaptation processes, with the potential for annotation 6,9 . The assessment of genomic signals of adaptation on non-model organisms is usually performed in two different ways, outlier analyses (OAs) and genotype-environment association analyses (EAAs) 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the tropicalization of NW Mediterranean can lead to a shift in dominance between the temperate common sea urchin Paracentrotus lividus, which will suffer from warming temperatures, and the thermophilous black sea urchin A. lixula (Carreras et al, 2020;Gianguzza et al, 2011;Wangensteen, Dupont, et al, 2013;. Such a shift can have drastic ecological impacts, as both species are conspicuous engineer species shaping benthic communities (Bulleri, Benedetti-Cecchi, & Cinelli, 1999;Bonaviri et al, 2011).…”
Section: Discussionmentioning
confidence: 99%